Diversified glucosinolate metabolism: biosynthesis of hydrogen cyanide and of the hydroxynitrile glucoside alliarinoside in relation to sinigrin metabolism in Alliaria petiolata - Frisch, Tina; Motawia, Mohammed S.; Olsen, Carl E.; Agerbirk, Niels; Møller, Birger L.; Bjarnholt, Nanna (Frontiers in Plant Science, 2015)
Alliaria petiolata (garlic mustard, Brassicaceae) contains the glucosinolate sinigrin as well as alliarinoside, a γ-hydroxynitrile glucoside structurally related to cyanogenic glucosides. sinigrin may defend this plant against a broad range of enemies, while alliarinoside confers resistance to specialized (glucosinolate-adapted) herbivores. Hydroxynitrile glucosides and glucosinolates are two classes of specialized metabolites, which generally do not occur in the same plant species. Administration of [UL-14C]-methionine to excised leaves of A. petiolata showed that both alliarinoside and sinigrin were biosynthesized from methionine. The biosynthesis of alliarinoside was shown not to bifurcate from sinigrin biosynthesis at the oxime level in contrast to the general scheme for hydroxynitrile glucoside biosynthesis. Instead, the aglucon of alliarinoside was formed from metabolism of sinigrin in experiments with crude extracts, suggesting a possible biosynthetic pathway in intact cells. Hence, the alliarinoside pathway may represent a route to hydroxynitrile glucoside biosynthesis resulting from convergent evolution. Metabolite profiling by LC-MS showed no evidence of the presence of cyanogenic glucosides in A. petiolata. However, we detected hydrogen cyanide (HCN) release from sinigrin and added thiocyanate ion and benzyl thiocyanate in A. petiolata indicating an enzymatic pathway from glucosinolates via allyl thiocyanate and indole glucosinolate derived thiocyanate ion to HCN. Alliarinoside biosynthesis and HCN release from glucosinolate-derived metabolites expand the range of glucosinolate-related defences and can be viewed as a third line of defence, with glucosinolates and thiocyanate forming protein being the first and second lines, respectively.